Multi-Objective Optimization of a Family House Performance and Forecast of its Energy Needs by 2100 - Serbouti, Abdelhadi; Rattal, Mourad; Boulal, Abdellah; Oualim, El Mostafa; Mouhsen, Azeddine (International Journal of Engineering and Technology, 2018)
This paper describes a general multi-objective optimization approach of the energy performance of buildings using genetic algorithms, and the forecast of future energy needs according to the IPCC climate change scenarios. To this end, the energy performance of a family house is optimized and the optimal solution is studied in a future context marked by global warming and rise of temperatures.Â Â Â